American internet companies' predicament in China - Lu, Jia (Javnost (Ljubljana), 2011)
This article analyses American Internet companies' predicament in China from the perspective of the Internet users. Google, eBay, and MSN Messenger were selected to represent American companies, and were compared with their major local competitors - Baidu, Taobao, and Tencent QQ. The demographic changes in the Internet user base and different choices of information have-more users and have-less users explain the rise and fall of American companies at the Chinese market. Have-more users and have-less users are respectively related to the space of flows and the space of places in Castells' (2000) notion. Moreover, this study found that have-more users have higher mobility to switchbetween the space of flows and the space of places than have-less users.Giddens' (1991) theory of emancipatory politics and life politics explain how individual users' self-identities affect the competition between local and American companies as well as the overall development of China's Internet.
Keywords: Kitajska; elektronski mediji; communication; komuniciranje; komunikacijska omrežja (računalništvo); internet; ponudba; konkurenca; ameriška podjetja